Drone Photographs of Pollinators in the Uppsala Region - Olofsson, Liv (Swedish University of Agricultural Sciences, 2025)
This dataset contains drone images of pollinators and plants collected in the Uppsala region of Sweden. The purpose of the data collection was to document pollinator activity in natural field environments, with the long-term goal of supporting research in automated species identification. The images include a variety of pollinator species, such as bees and butterflies, as well as diverse plant species commonly found in the area.

The dataset can be used to train and evaluate models for classification of both pollinators and plant species, and it is particularly useful for research related to biodiversity monitoring, ecological field studies, and automated detection systems. Because the images are obtained from natural field sites rather than controlled laboratory settings, they offer realistic environmental conditions and therefore provide valuable challenges for algorithm development.

The images were collected specifically for this project in order to support research on drone-based pollinator monitoring. They have not been used in previous studies, and no publications have been produced from this dataset at the time of submission. The dataset is intended to be openly available for future research and methodological development.

The images were taken with a Drone, specifically DJI mini 4 Pro by Liv Olofsson, Research Assistant at SLU.

Detta dataset innehåller drönarbilder av pollinatörer och växter insamlade i Uppsalaregionen. Syftet med datainsamlingen var att dokumentera pollinatörers aktivitet i naturliga fältmiljöer, med det långsiktiga målet att stödja forskning inom automatisk pollinatör-identifiering. Bilderna omfattar olika pollinatörarter, såsom bin och fjärilar, samt en mångfald av växtarter som är vanliga i området.

Datasetet kan användas för att träna och utvärdera modeller för klassificering av både pollinatörer och växtarter och är särskilt användbart för forskning som rör biodiversitetsövervakning, ekologiska fältstudier och automatiserade detektionssystem. Eftersom bilderna har samlats in i naturliga miljöer snarare än i kontrollerade laboratorieförhållanden, erbjuder de realistiska omständigheter och därmed värdefulla utmaningar för algoritmutveckling.

Bilderna samlades in specifikt för detta projekt för att stödja forskning om drönarbaserad pollinatör-övervakning. De har inte använts i tidigare studier, och inga publikationer har producerats från detta dataset vid tidpunkten för inlämningen. Datasetet avses vara öppet tillgängligt för framtida forskning och metodutveckling.

Bilderna var tagna med drönare, specifikt DJI mini 4 Pro av Liv Olofsson, forskningsassistent på SLU.
Drönarfoton av pollinatörer i Uppsala region
Keywords: machine learning; maskininlärning; artificial intelligence; artificiell intelligens; agricultural land; jordbruksmark; insects; insekter; pollinators; pollinatörer; uppsala; uppsala; växter; plants; blommor; flowers; drone imagery; drönarbilder; field diversity; fältdata; biodiversitet; biodiversity; Agricultural Science; Jordbruksvetenskap; Artificial Intelligence; Artificiell intelligens